Testing the impact of non-destructive DNA extraction on setae structure of Amphipoda (Crustacea) - Timm, Roxana; Schwentner, Martin; Bober, Simon; Lörz, Anne-Nina (Zootaxa, 2021)
Intact voucher specimens are essential to allow detailed morphological observations on specimens that are used in molecular genetic studies. This can be achieved either by dissection of small, taxonomically uninformative parts of the body for DNA extraction or by employing non-destructive DNA extraction methods. The latter is particularly important for small-bodied animals. Here we test the effects of Chelex-based DNA extraction on the integrity of setae and setules in Amphipoda, fragile structures of great taxonomic importance. Our results show that DNA extraction using Chelex had no influence on the setae and setule structure and is well suited for reverse taxonomic approaches and the long-term storage of morphological vouchers. A detailed protocol for non-destructive DNA extraction is provided.